A Comprehensive Approach to Cultivating Character Values Based on the Santri Trilogy in Madrasah Ibtidaiyah - Rofiq, As'adur; Saihan, Saihan; Istifadah, Istifadah (ATTA`DIB, 2025)
This study aims to analyze the implementation of the values of the Trilogy of Santri - responsibility for fardhu 'ain obligations, honesty in avoiding major sins, and noble character towards God and His creatures - at MI Raudhatul Muta'alimin Jember. Using a qualitative approach with a case study design, this research explores the application of formal, hidden curriculum, and habituation programs in shaping student character. The results show that this integrative approach is effective in increasing students' awareness in carrying out religious obligations (85%), reducing dishonest behavior (decreased from 15% to 3%), and improving social interaction and environmental awareness (90%). This approach is supported by Kohlberg's moral development theory, Lickona's character education, and Gardner's multiple intelligences. This research makes a significant contribution to the development of a character education model based on pesantren values in the formal education system, especially at the primary education level.